Rise and shine for eating right: the link between healthy nutrition and chronotype among young adults - Mortaş, Hande; Ayhan, Büşra; Navruz Varlı, Semra; Köse, Süleyman; Ağagündüz, Duygu; Bilici, Saniye (Frontiers in Nutrition, 2023)
Aim: Many studies have examined the relationship between chronotype and general health. Because healthy eating is the basis of health aim of this study is to evaluate the relationship between healthy nutrition attitudes and chronotype in young adults. Methods: This cross-sectional study was conducted with 1400 young adults (936 females and 464 males). Chronotype was assessed by the Turkish version of the Morningness-Eveningness Questionnaire (MEQ) and the Attitude Scale for Healthy Nutrition (ASHN) was applied by face-to-face interview. Furthermore, 24-h dietary recall was collected. The scores of nutrient adequacy ratio (NAR) and mean adequacy ratio (MAR) were calculated. The anthropometric measurements including body weight and height were taken. Results: The chronotype distribution of participants according to the MEQ score and MAR score were not significantly different between females and males (p>0.05). The percentage of participants with high healthy eating attitude was lowest in the evening chronotype and highest in the morning chronotype (49.7%, 37.7% and 25.4% in morning-, intermediate-, evening-types, respectively; p=0.000 for all groups according to the reciprocal comparisons). There was a positive correlation of the MEQ scores with the scores of ASHN (r=0.282, p<0.01). ASHN score was shown to be a predictor for MEQ score (β=0.280, p=0.000). Moreover, the score of "poor eating habits" was shown to be highest in the evening chronotype and lowest in the morning chronotype (14.9±3.0 and 13.1±3.0, respectively; p<0.01). Conclusions: The results of this study indicate that individuals with the evening chronotype are more deficient in terms of healthy nutrition attitudes. Further studies with larger populations will potentially guide the development of health promotion strategies to prevent and treat chronic diseases based on an individual's chronotype.